Pengaruh Kemudahan Transaksi, Kepercayaan, Kenyamanan, Dan Desain Antarmuka Terhadap Minat Nasabah Menggunakan Aplikasi Blu BCA - Ariyani, Ida; Hermanto, Rudi (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2025)
This study discusses the Influence of Ease, Trust, Comfort and Interface Design. The purpose of this study is to determine how much interest customers have in using the BluBCA application. This study was conducted at PT BCA Tbk Dewi Sartika Branch Office, East Jakarta 13630. This study uses a descriptive research design through a quantitative approach with data collection using a purposive sampling technique with Krejcie table guidelines. The population taken in this study were BCA priority customers of KCP Dewi Sartika who had not used Blu BCA. The number of BCA Priority Dewi Sartika customers is 192 customers, 139 of whom have not used the BluBCA application (source: BCA internal data), the sample used was 103 customers with Krejcie table guidelines and the data processing technique uses the JASP application, an abbreviation of Jeffreys's Amazing Statistics Program, a statistical analysis software by the Department of Psychological Methods, University of Amsterdam, Netherlands. This open-source and multi-platform program is the choice for students and researchers. JASP is an easy-to-use software option with complete features. From the results of the research of multiple linear regression equations as follows, Y = 1.793 + 0.186 X1 + 0.289 X2 - 0.047 X3 +0.343 X4+e from the calculation, it can be seen that, the variables of Ease, Trust, Comfort and Interface design have an effect on customer interest in using the BluBCA application, but there is a difference in this study where the effect of comfort on the interest produced in this study is not significant.